Validation and in silico function prediction of circtial1 as a novel marker of abnormal lung development in nitrofen-induced congenital diaphragmatic hernia (CDH) - Jank, Marietta; Kraljevic, M.; Ozturk Aptekmann, A.; Patel, D.; Boettcher, Michael; LeDuc, R.; Keijzer, R. (Pediatric surgery international, 2025)
Purpose Circular RNAs (circRNAs) are stable, non-coding RNAs with tissue- and developmental-specific expression making them suitable biomarkers for congenital anomalies. Current circRNA discovery pipelines have focused on human and mouse. We aim to bridge this gap by combining bioinformatics resources and used circtial1 as a model candidate in the nitrofen rat model of congenital diaphragmatic hernia (CDH). Methods Circtial1 backsplice junction sequences from a microarray were used to predict mature circRNA sequences and downstream pathways by miRNA interactions using CRAFT and circAtlas. We validated circtial1 expression using conventional PCR, amplicon sequencing, RT-Qpcr, and Basescope™ in situ hybridization. Results Expression of parental gene tial1 was decreased in nitrofen-induced lungs at embryonic day (E)15 (p = 0.004) and E21 (p = 0.008), while at E18, there was no significant difference (p = 0.65). At E21, circtial1 expression did not differ between CDH and control lungs (p = 0.07); however, there was a decreased expression in male pups (p = 0.0167). In situ hybridization confirmed low circtial1 expression. CircRNA::miRNA::mRNA interactions revealed pathway enrichment for inflammation/infection and neuron function/development. Conclusion For the first time, we report circRNA profiling in nitrofen-induced CDH with a sex-specific expression of circtial1. Current bioinformatics tools have significant challenges, but can guide hypothesis formation on their biological role.
Online veröffentlicht: 21. Dezember 2024
Gesehen am 10.04.2025